Effects of positive human contact on fear and physiological stress responses in Pekin ducks (Anas platyrhynchos domesticus) subjected to crating and transport - Mitin, Helen; Idrus, Zulkifli; Meng, Goh Yong; Sazili, Awis Qurni; Awad, Elmutaz Atta (Elsevier BV, 2023)
A growing body of research shows that farm animals frequently seek and enjoy human interaction. However, there is a lack of information on how positive human contact affects ducks' stress and fear responses. An experiment was conducted to compare the effects of positive human contact on tonic immobility (TI) duration, serum levels of corticosterone (CORT) and heat shock protein (HSP) 70 in male Pekin ducks (Anas platyrhynchos domesticus) subjected to crating or road transport. The growth performance of the ducks was also determined. In this experiment, 600 day-old male Pekin ducklings were equally assigned to one of the following human contact treatments; (1) ducks were picked up individually and stroked gently for 30 s once daily in their home pen from day 1 to day 42 (P1“42); (2) ducks were picked up individually and stroked gently for 30 s once daily in their home pen from day 1“21 (P1“21); (3) ducks were picked up individually and stroked gently for 30 s once daily in their home pen from day 21“42 (P21“42); or (4) the ducks did not receive human contact other than the routine husbandry (NC). On day 42, ducks from each experimental group were exposed to one of three conditions: crating for 3 hours, road transportation for 3 hours, or basal conditions in which they remained undisturbed in their home pens. The P21“42 ducks exhibited higher levels of stress and fear than the P1“42 and P1“21 ducks, as indicated by CORT and TI duration measurements following crating or transport. The P1“42 and P1“21 ducks exhibited higher levels of HSP70 expression than the NC group under both basal conditions and after being subjected to crating and transportation. In conclusion, this study demonstrates the beneficial effect of positive human contact from days 1“21 or days 1“42 in enhancing resilience to crating and transportation in ducks.